Pengembangan Sistem Replikasi dan Redundansi untuk Meningkatkan Kehandalan Basisdata MySQL - Dolly Simon Kristian; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
With the development of information technology, humans make it easy to complete every duty. Any information about the work carried out to be very valuable, therefore the information should be stored properly, by organizing a reliable database system when performing data storage on the server information. Build a design application virtualization master slave database servers that are connected with the management node using the virtual application to get the test results replication system performance and redundancy in the design of the cluster system. Methodology of this research include the study of literature, collecting data by interview, observation, literature studies, system design, and testing of the system. In a literature study on the use of research methods to study the literature books, records that can be used as a support in the research. The design of this thesis using MySQL Cluster system with Ndbcluster engine. Last is testing this system on its performance on the server failure or failures occur and reliability in performance. The results obtained are when there is a failure on the primary server, it will be immediately replaced by another server is a slave. And the replication of data between the main server and slave.